1996
DOI: 10.1007/bf00120221
|View full text |Cite
|
Sign up to set email alerts
|

The hybrid origin of the polyploid liverwort Pellia borealis

Abstract: Ab~ra~Isozyme markers were used to investigate the origin of the polyploid liverwort, Pellia borealis (gametophytic n -18), which was believed to represent an autopolyploid form of Pellia epiphylla (n -9). Enzyme variation was studied in four taxa: polyploid P. borealis, two recently discovered sibling species of P. epiphylla complex, and the closely related P. neesiana (n -9). (3ametophytes of the polyploid showed a complex electrophoretic phenotype for three diagnostic enzymes (DIAl, MPI1 and ACO) in contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…These reports are distributed randomly through the phylogeny of liverworts and include some genera: Ricca [69], Marchantia [70], Plagiochasma [71], Porella [72] and Pellia [73], but did not include epiphyllous liverworts with the putative exception of Trocholejeunea [74]. The absence of evidence may be a result of the limited cytological studies or special life cycle period-haploid gametophyte.…”
Section: Discussionmentioning
confidence: 99%
“…These reports are distributed randomly through the phylogeny of liverworts and include some genera: Ricca [69], Marchantia [70], Plagiochasma [71], Porella [72] and Pellia [73], but did not include epiphyllous liverworts with the putative exception of Trocholejeunea [74]. The absence of evidence may be a result of the limited cytological studies or special life cycle period-haploid gametophyte.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to answer the question about progenitors of allopolyploid Calypogeia species more specimens from a wider range of geographic distribution have to be analyzed. Isozyme studies allowed to indicate progenitor species in the case of Porella baueri [10] and Pellia borealis [23]. In Calypogeia it is especially difficult since the genus comprises about 90 described species [2].…”
Section: Discussionmentioning
confidence: 99%
“…The species have been designated species S and N (Szweykowski & Odrzykoski, 1990). Odrzykoski et al . (1996) found that the (gametophytically) diploid species, P. borealis , displayed fixed heterozygosity at three isozyme loci: Mpi1 , Dia1 and Aco .…”
Section: Sibling Speciation In Liverwortsmentioning
confidence: 99%